Growth Factors in Inflammatory Bowel Disease. (1st June 1996) - Wright, Nicholas
Abstract : Growth factors have many influences on the gastrointestinal tract, not just modulating cell proliferation, but also acting on other aspects of physiology. Several of these functions are incriminated in the pathogenetic and healing phenomena that accompany inflammatory bowel disease (IBD). A review of growth regulation in the intestine is presented. Topics include growth phenomena in IBD, sources of growth factors, growth factors in gut growth responses, trefoil peptides, other growth factors and role of growth factors in IBD.